Relationship between circular economy practices and process innovation: an analysis of textile organizations in Santa Catarina - Langa, Emanuel Devigili (2024)
Objective: To evaluate the relationship between circular economy practices and process innovation. Methodology: This is a quantitative study using descriptive, exploratory, and confirmatory approaches. It is a cross-sectional study employing a survey typology. The study utilized a questionnaire encompassing the dimensions of process innovation and circular economy (EC), applied to a sample of 135 textile industry companies. Data analysis was conducted through Structural Equation Modeling (SEM). Findings: There is an evident positive relationship between EC practices and process innovation. The results indicate that the surveyed textile industries are in the initial phase of implementing their EC practices. Research Limitations: The use of a non-probabilistic sample, thus hindering the generalizability of the results and focusing solely on process innovation. Theoretical Implications: Development and psychometric validation of the questions guiding the study of circular economy application through the ReSOLVE model, as well as integration with the construct of process innovation. Social Implications: By applying the principles of the circular economy through the ReSOLVE model, there is optimization of production, and coupled with technological development, textile industries achieve better process innovation outcomes. Managerial Implications: Real evidence from the application of the ReSOLVE model demonstrates the cause-and-effect relationship between the circular economy and process innovation. Originality/Value: The theoretical relationship between EC and innovation and the psychometric validation process of the questions guiding the study of EC application through the ReSOLVE model.